FOMO’s Impact on Impulsivity: The Mediating Role of Flash Sale Promotional Strategies - Erick Karunia; Azis, Muh. Irfandy; Faerozh Madli; Mohd Noor Hidayat Jimainal; Ang Hong Loong (Fakultas Ekonomi dan Bisnis, Universitas Tarumanagara, 2025)
This study explores the impact of Fear of Missing Out (FOMO) on impulsive buying behaviour among e-commerce consumers in Indonesia. Using an online survey involving 349 active e-commerce users in Indonesia, the study examines levels of FOMO, frequency of impulsive purchases, and perceptions of flash sale promotions. Data analysis using Structural Equation Modelling (SEM) AMOS reveals that FOMO significantly positively affects impulsive buying behaviour, with flash sale strategies amplifying this relationship. Furthermore, demographic factors such as age, digital literacy levels, and social influence are found to moderate this relationship. The findings underscore the importance of understanding consumer psychology in designing effective and ethical marketing strategies. Thus, this study contributes to the existing literature on consumer behaviour and has significant implications for marketers, e-commerce platforms, and policymakers.